Education, Household and Society Impact on the Level of Information about Contraceptive Methods (Papeles, 2016)
This paper presents research on the relationship between the knowledge of contraceptive methods thbarrinformational role of the school, being public or private. This analysis included a population of 192 teenagers (15 to 18 years old) from six schools. A survey was applied in which questions related to theoretical knowledge about contraceptive methods and socio-economic and cultural variables are answered.
Keywords: contraceptive methods; teenagers; sexuality; socioeconomic; household; public school; private school; sex education; marginality